Recensione di Sergio YONA, Gregson DAVIS, Epicurus in Rome: Philosophical Perspectives in the Ciceronian Age - Margherita Erbì (Ciceroniana On Line, 2023)
Recensione di Sergio YONA, Gregson DAVIS, Epicurus in Rome: Philosophical Perspectives in the Ciceronian Age, Cambridge University Press, Cambridge-New York 2022, 207 pp. ISBN 9781108845052.